Infant feeding methods among HIV-positive mothers in Yei County, South Sudan - Anthony Yousepha Lasuba (Health and Social Sciences Research Institute - South Sudan (HSSRI-SS), 2016)
Introduction: This study describes the infant feeding methods chosen by HIV-positive mothers in Yei County, South Sudan and the factors that influenced their choice. Methods: This cross-sectional study used quantitative and qualitative methods to collect data from a sample of HIV positive mothers from Yei Hospital Mother and Child Health (MCH) section, and St Bakhita Primary Health Care Centre. Results: The results showed that the mothers' levels of correct knowledge about HIV transmission to infants, and infant feeding guidelines to prevent transmission were high. Most mothers chose exclusive breastfeeding. Conclusions: The factors which were significantly associated with the choice of infant feeding methods included: marital status, level of education, income, knowledge about prevention of mother-to-child transmission of HIV, cultural beliefs, social stigma and cost of infant feeding method.